Security Standardisation Research : Second International Conference, SSR 2015, Tokyo, Japan, December 15-16, 2015, Proceedings - Chen, Liqun; Matsuo, Shin'ichiro.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the Second International Conference on Security Standardisation Research, SSR 2015, held in Tokyo, Japan, in December 2015. The 13 papers presented in this volume were carefully reviewed and selected from 18 submissions. They are organized in topical sections named: bitcoin and payment; protocol and API; analysis on cryptographic algorithm; privacy; and trust and formal analysis. .
Keywords: Computer security; Data encryption (Computer science).; Computer Communication Networks; Software engineering; Data structures (Computer scienc; Computer science; Systems and Data Security; Cryptology; Computer Communication Networks; Software Engineering; Data Structures; Math Applications in Computer Science